University Mathematics Content Courses and Elementary Prospective Teachers: A Review of Research from 1990 to 2014. (2nd January 2019) - Auslander, Susan Swars; Hart, Lynn C.; Carothers, Jody; Jacobs, Tiffany; Chestnutt, Cliff
ABSTRACT: This project reviewed the state of the research drawing from articles published from 1990 to 2014 (25 years) with elementary prospective teachers (EPTs) as participants, who were completing university courses focused on mathematics content. Twenty-four studies met the inclusion criteria for the review. Of these studies, 11 examined noncognitive factors such as beliefs, attitudes, motivation, and identity, 10 investigated mathematical knowledge in various forms, two explored noncognitive factors and mathematical knowledge, and one examined classroom norms and mathematical justification. Nineteen of the 24 studies occurred in the context of courses categorized as involving alternative pedagogy. The analysis revealed positive changes in EPTs' affect (e.g., beliefs, attitudes, emotions) were possible as a result of course experiences, but these shifts were sometimes difficult to come by and encountered resistance from EPTs. Some studies showed an increase in EPTs' content knowledge across the courses, whereas others did not achieve the desired effects. Implications for course learning experiences are offered.